Pengaruh Media Pembelajaran Berbasis TIK pada Materi Tema 7 Subtema 1 Kelas 4 tentang Macam-Macam Gaya terhadap Hasil Belajar Kognitif Siswa dalam Pembelajaran Daring pada Masa Pandemi Covid-19 - Dewanto, Mohammad Fajar Mak’ruf Winyam; Efendi, Nur (Indonesian Journal Publisher, 2024)
From March 2020 to April 2021, the COVID-19 pandemic was still ongoing, which led to the continued closure of schools and the implementation of remote or online learning by all educational institutions. This research aims to describe the influence of ICT-based learning media on the topic of various forces in Theme 7, Sub-theme 1, for 4th-grade elementary school students on their cognitive learning outcomes during online learning amidst the COVID-19 pandemic. This study employed a quantitative experimental method with a one-group pre-test and post-test design. Data collection was conducted through testing methods, where pretests and post-tests were administered to assess students' learning outcomes and to determine the significant impact of using ICT-based learning media on their cognitive learning. The paired sample pre-test results showed a significance level (2-tailed) of 0.000, which aligns with the t-Test decision rule indicating that when the sig. (2- tailed) value is below 0.05, there is a significant increase or influence on the research variable. Therefore, it can be concluded that the use of ICT-based learning media for the topic of various forces in Theme 7, Sub-theme 1, has a significant impact on the cognitive learning outcomes of 4th-grade elementary school students.